A route to support Pt sub-nanoparticles on TiO2 and catalytic hydrogenation of quinoline to 1, 2, 3, 4-tetrahydroquinoline at room temperature. Issue 17 (15th August 2018) - Li, Shaopeng; Yang, Youdi; Wang, Yanyan; Liu, Huizhen; Tai, Jing; Zhang, Jing; Han, Buxing
Abstract : We report a method to support Pt sub-nanoparticles on TiO2 . Abstract : We report a method to support Pt sub-nanoparticles on TiO2 . The feature of this route was that N, N ′-(ethane-1, 2-diyl)diformamide (ED) acted as both the reducing agent and stabilizing agent. The yield of 1, 2, 3, 4-tetrahydroquinoline could be higher than 99% at room temperature. In addition, the catalyst can be recycled at least 4 times.